Monocyte-to-albumin ratio as a novel predictor of long-term adverse outcomes in patients after percutaneous coronary intervention. Issue 7 (30th July 2021) - Zhang, Zeng-Lei; Guo, Qian-Qian; Tang, Jun-Nan; Zhang, Jian-Chao; Cheng, Meng-Die; Song, Feng-Hua; Liu, Zhi-Yu; Wang, Kai; Jiang, Li-Zhu; Fan, Lei; Yue, Xiao-Ting; Bai, Yan; et al.
Abstract: Background: Monocyte count and serum albumin (Alb) have been proven to be involved in the process of systemic inflammation. Therefore, we investigated the prognostic value of monocyte-to-albumin ratio (MAR) in patients who underwent percutaneous coronary intervention (PCI). Methods: We enrolled a total of 3561 patients in the present study from January 2013 to December 2017. They were divided into two groups according to MAR cut-off value (MAR < 0.014, n =2220; MAR ≥ 0.014, n =1119) as evaluated by receiver operating characteristic (ROC) curve. The average follow-up time was 37.59 ± 22.24 months. Results: The two groups differed significantly in the incidences of all-cause mortality (ACM; P< 0.001), cardiac mortality (CM; P< 0.001), major adverse cardiovascular events (MACEs; P= 0.038), and major adverse cardiovascular and cerebrovascular events (MACCEs; P= 0.037). Multivariate Cox regression analyses revealed MAR as an independent prognostic factor for ACM and CM. The incidence of ACM increased by 56.5% (hazard ratio [HR] = 1.565; 95% confidence interval [CI], 1.086–2.256; P= 0.016) and that of CM increased by 76.3% (HR = 1.763; 95% CI, 1.106–2.810; P= 0.017) in patients in the higher-MAR group. Kaplan–Meier survival analysis suggested that patients with higher MAR tended to have an increased accumulated risk of ACM (Log-rank P< 0.001) and CM (Log-rank P< 0.001). Conclusion: The findings of the present study suggested that MAR was a novel independent predictor of long-term mortality in patients who underwent PCI.